Multi-institutional Analysis of Recurrence and Survival After Neoadjuvant Chemoradiotherapy of Esophageal Cancer: Impact of Histology on Recurrence Patterns and Outcomes. Issue 4 (April 2019) - Xi, Mian; Yang, Yadi; Zhang, Li; Yang, Hong; Merrell, Kenneth W.; Hallemeier, Christopher L.; Shen, Robert K.; Haddock, Michael G.; Hofstetter, Wayne L.; Maru, Dipen M.; Ho, Linus; Wu, Carol C.; et al.
Abstract : Objective: To determine the impact of histology on pathologic response, survival outcomes, and recurrence patterns in patients with esophageal cancer (EC) who received neoadjuvant chemoradiotherapy (CRT). Summary of Background Data: There is a paucity of data regarding comparative outcomes after neoadjuvant CRT between esophageal squamous cell carcinoma (SCC) and adenocarcinoma. Methods: Between 2002 and 2015, 895 EC patients who underwent neoadjuvant CRT followed by esophagectomy at 3 academic institutions were retrospectively reviewed, including 207 patients with SCC (23.1%) and 688 patients with adenocarcinoma (76.9%). Pathologic response, survival, recurrence pattern, and potential prognostic factors were compared. Results: Pathologic complete response (pCR) rate was significantly higher for SCC compared with adenocarcinoma (44.9% vs 25.9%, P < 0.001). After a median follow-up of 52.9 months, 71 patients (34.3%) with SCC versus 297 patients (43.2%) with adenocarcinoma had recurrent disease ( P = 0.023). For patients who achieved a pCR, no significant differences were found in recurrence pattern, sites, or survival end-points between the 2 histology groups. For non-pCR patients, the SCC group demonstrated significantly higher regional and supraclavicular recurrence rates but a lower hematogenous metastasis rate than adenocarcinoma patients, whereas the adenocarcinoma patients had a more favorable locoregional failure-free survival ( P = 0.005) and worse distant metastasis-free survival ( P = 0.024). No differences were found in overall survival ( P = 0.772) or recurrence-free survival ( P = 0.696) between groups. Conclusions: SCC was associated with a significantly higher pCR rate than adenocarcinoma. Recurrence pattern and survival outcomes were significantly different between the 2 histology subtypes in non-pCR patients. Abstract : Supplemental Digital Content is available in the text